SPATIAL ANALYSIS OF LAND USE SUITABILITY AGAINST REGIONAL SPATIAL PLANNING AT THE FOOD ESTATE PLANNING SITE IN PULANG PISAU REGENCY, CENTRAL KALIMANTAN - Budianto, Budianto; Setiadi, Hafid; Dimyati, Muhammad; Supriatna, Supriatna (UI Scholars Hub, 2022)
The limited space on land increases the important of spatial planning that is transparent, accountable and effective, which involves multi-stakeholders in its conception. Such planning is intended to create spatial arrangement that supports security, productivities and sustainability. In the attempt to secure food supply in the future, the government of Indonesia has initiated Food Estate program in 2020 which occupy some vast areas. By occupying large area, careful spatial planning and its proper implementation is highly important for a successful program. This study is a survey to the land use and land utilization in one of the planned areas for food estate project in Pulang Pisau Regency, Central Kalimantan, and evaluate their suitability with the designated spatial planning. There is 39.598,95 Ha or 61,24 % of the total land use that suitable with the spatial planning and 25.064,75 Ha or 38,76 % that is not suitable. It is expected that as the food estate program is rolling, the suitability percentage will increase and lead to the successful production of food supplies.